Pengembangan Keterampilan SDM Melalui Kewirausahaan Digital: Optimalisasi Gastrowisata Tape Singkong Desa Wargamekar - Rahmat, Taufiq; Faujiyyah, Dini; Fasha, Asep Raida; Hadidawati, Hadidawati; Yusuf, Dadang; Anareksa, Hari Sena (PT. Riset Press International, 2023)
The digital entrepreneurship-based human resource development program has been implemented in Wargamekar Village with the aim of enhancing the potential of cassava tape gastronomic tourism. This article addresses the challenges faced by cassava tape entrepreneurs regarding their limited understanding of the importance of digital technology adoption and branding in business development. The implementation method encompasses activities such as introducing the concepts of gastronomic tourism, digital entrepreneurship, social media marketing, as well as field mentoring. Consultation sessions and coaching provide personal guidance in developing digital skills and branding strategies. The program evaluation results indicate a high level of participant satisfaction. Participants have gained an understanding of gastronomic tourism concepts and the utilization of digital technology to optimize cassava tape businesses. Field mentoring enriches the history of cassava tape and enhances participants' comprehension of local cultural values. Consultation sessions and coaching have successfully developed a stronger brand identity and branding strategy. Recommendations for further activities include expanding field mentoring and broadening the topics covered in consultation and coaching. This program is expected to continue benefiting cassava tape entrepreneurs in Wargamekar Village and enhancing the potential of cassava tape businesses in the digital era.